2016
DOI: 10.1177/0956462416645727
|View full text |Cite
|
Sign up to set email alerts
|

Peru's HIV care continuum among men who have sex with men and transgender women: opportunities to optimize treatment and prevention

Abstract: The HIV epidemic in Peru is concentrated in men who have sex with men (MSM) and transgender women (TW), who have an estimated prevalence > 10%, while the overall population prevalence remains < 1%. Because MSM and TW account for >60% of new infections, it is crucial to understand the full HIV continuum of care for these key populations. We performed a review of the peer-reviewed scientific and grey literature to determine the proportion of HIV-infected MSM and TW in Peru who are diagnosed, linked to and retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 37 publications
1
48
1
1
Order By: Relevance
“…However, little is known about HIV linkage and care outcomes for transwomen, in part, because data about trans women are usually grouped together with men who have sex with men (MSM). For example, a recently published study from Peru found low HIV status awareness, retention in care, uptake of ART and virologic suppression among transwomen and MSM [6]. …”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about HIV linkage and care outcomes for transwomen, in part, because data about trans women are usually grouped together with men who have sex with men (MSM). For example, a recently published study from Peru found low HIV status awareness, retention in care, uptake of ART and virologic suppression among transwomen and MSM [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only 60% of the participants reporting that they were HIV positive at baseline also reported being on ART (data not shown). The best estimate for the care cascade among MSM and transgender women in Peru is that 12% have achieved virologic suppression(26). Although HIV positive individuals on treatment with an undetectable viral load are much less likely to infect their partners(27), this can only work in the presence of effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For TGW, the proportion that know their HIV serostatus is unknown because studies in Peru have often historically combined data specific to TGW under the ‘MSM’ label 10. A recent scoping literature review found that among Peruvian MSM and TGW living with HIV, only 24% knew their infection status, of which 13.6% were receiving ARV and 12% had achieved viral suppression 12. The authors point out that the largest ‘drop-off’ occurred at the beginning: identifying those who are infected with HIV.…”
Section: Introductionmentioning
confidence: 99%